Potensi Pengembangan Desa Kliwonan sebagai Desa Wisata Batik di Kabupaten Sragen - Ninik Wahyuning Tyas; Maya Damayanti (P4W LPPM IPB, 2018)
Nowadays, tourism village development has become an alternative for local economic development and been applied in many regions, including at Kliwonan Village in Sragen Regency, as a part of Sragen Batik Cluster. Kliwonan Village has development potentials viewed from its geographical and accessibility aspect. Viewed from geographical aspect, Kliwonan Village is approximately 10 km from Sangiran Museum, which was established as a National Tourism Strategic Area (KSPN). Moreover, viewed from the accessibility aspect, Kliwonan Village is easily accessible since is approximately 8 km from Solo-Kertosono toll exit. In order to be developed as a batik tourism village, a comprehensive review of supply and demand is needed. Based on that, this research aimed to explore the development potentials of Kliwonan Village as a batik tourism village based on the aspects of supply and demand in order to contribute recommendations for Kliwonan Village’s development in the future. This research used mixed method, incorporating qualitative method to analyze tourism supply-side, community characteristic, and policy, as well as quantitative method to analyze tourism demand-side. This research indicates that Kliwonan Village has the potential to be developed as a batik tourism village. However, it is still not ready since there are some elements in the supply-side that need improvement or development, namely accessibility, amenity, information and institution.